Optimization of design and technological parameters of the rotary body for inter-row cultivation - Браженко, Светлана Аналольевна (Technology audit and production reserves, 2013)
This article is devoted to research of indicator dependence of inter-row cultivation quality on parameters of improved design rotary working body. Analysis of the results of known theoretical and experimental research has been conducted. Aims and objectives of following research were formulated. Kinematic analysis and derivation of graph-analytic dependencies of throw out of soil under the influence of the rotary working body with a vertical axis of rotation were conducted. The theoretical results are verified by the means of experiments. The regression analysis of the results of experiments allowed to establish optimal parameters of axis angle of the rotor and its angular velocity. Well-grounded parameters provide the minimum content of erosion-prone soil particles and a minor deviation from the horizontal surface profile.